THE RELATIONSHIP BETWEEN ADVANCED CHRONIC VENOUS DISEASE, PSYCHOPATHOLOGY, AND QUALITY OF LIFE - Correia, Ricardo (2021)
Introduction: Chronic venous disease (CVD), particularly if severe, can have significant psychopathologic consequences and major changes in quality of life. Anxiety and humor disturbances are often already present when the patient with CVD searches the vascular surgeon. This study aims to identify and characterize psychopathology in CVD and its relation with quality of life. Methods: A transversal study included all patients seen in the first appointment with two vascular surgeons of a tertiary university hospital, with the CVD diagnosis, from December 2019 to January 2021. Five Portuguese language-validated questionnaires were used: EQ-5D (Euro quality of life – 5 Dimensions), EQVAS (Euro QoL visual analogue scale), CIVIQ20 (chronic venous insufficiency questionnaire), BAI (Beck Anxiety Inventory) and BDI (Beck's Depression Inventory). The primary endpoints were anxiety and humor disturbances’ suggestive scores, evaluated on BAI and BDI question- naires, respectively. The secondary endpoints were quality of life, evaluated on EQ-5D, EQVAS and CIVIQ20 questionnaires. The findings were correlated according to the clinical class (C) of the CEAP classification (clinical, etiological, anatomical and pathophysiological). Results: Fifty-nine patients were included. The median age was 58 years. 73% were female. 20% was under psychiatric pills. The CEAP clinical classification was as follows: C1 7%; C2 64%; C3 10%; C4 15%; C5 2%; C6 2%. The median CIVIQ20 and EQVAS scores were 48 and 75, respectively. The median BAI score was 16; 40% of the patients stated moderate or potentially worrying anxiety levels. The median BDI score was 7; 31% of the patients stated at least mild levels of depression. There was a positive correlation between the clinical class CEAP and the BAI score (p=0,049) and the BDI score (p=0,039). There was no correlation between the clinical class CEAP and the EQVAS score. The patients with higher CIVIQ20 scores have chosen lower scores on EQVAS (p<0,001). There was a positive correlation between the CIVIQ20 score and BAI score (p<0,001) and the BDI score (p=0,003). The patients with worse ascertained health on EQVAS displayed higher anxiety (p=0,009) and depression scores (p<0,001). There was a positive correlation between BAI and BDI scores (p=0,002). Conclusion: Anxiety and depression disturbances commonly coexist and are prevalent in symptomatic CVD patients. The relation between severe clinical signs of CVD, lower quality of life and the presence of psychopathology was demonstrated in this study, which suggests the need for an adjunctive psychological approach to CVD patients.